A turn-on fluorogenic chemosensor for Fe3+ and a Schottky barrier diode with frequency-switching device applications. Issue 4 (22nd March 2018) - Molla, Habib Ali; Bhowmick, Rahul; Islam, Abu Saleh Musha; Show, Bibhutibhushan; Mukherjee, Nillohit; Mondal, Anup; Ali, Mahammad
Abstract : A novel highly sensitive and selective fluorescent chemosensorL has been synthesized and characterized by various physicochemical techniques. Abstract : A novel highly sensitive and selective fluorescent chemosensorL has been synthesized and characterized by various physicochemical techniques. In 3 : 7 water : MeCN (v/v) at pH 7.2 (10 mM HEPES buffer, μ = 0.05 M LiCl), it selectively recognizes Fe 3+ through 1 : 1 complexation resulting in a 106-fold fluorescence enhancement and a binding constant of 8.10 × 10 4 M −1 . The otherwise non-fluorescent spirolactam form of the probe results a dual-channel (absorbance and fluorescence) recognition of Fe 3+ via CHEF (chelation enhanced fluorescence) through the opening of the spirolactam ring. We have also carried out fluorescence titration and anisotropy ( r ) studies in pure water in the presence of SDS (sodium dodecyl sulphate). Based on the dependence of FI (fluorescence intensity) and r on [SDS] it was proposed that the probe is trapped between two SDS monolayers which again interact among themselves by π⋯π stacking. As a result, there is an increase in FI up to [SDS] ∼ 7 mM – a phenomenon reminiscent of aggregation-induced enhancement of emission (AIEE). Beyond this concentration of SDS (7 mM), micelle formation takes place and the π⋯π stacked polymer now becomes a monomer and is trapped inside the micellar cavity. As a result, there is a decrease in FI at [SDS] > 7 mM. But for anisotropy, it increases with [SDS] beyond 7 mM. Ligand, metal, and SDS interactions are well established through different optical and morphological studies. [L –Fe(NO3 )] 2+ thin films on FTO (Fluorine-doped Tin Oxide) glass substrates have been designed with the help of the spin-coating deposition technique. The deposited film of thickness 1.6 × 10 −5 cm is well characterized by optical band gap calculation with a direct band gap, ε g ∼ 1.6 eV. FESEM was also performed for the [L –Fe(NO3 )] 2+ /FTO film. The current–voltage characteristics were measured by the two-probe technique. Light-dependent exciton generation was carried out by taking the top and bottom contacts with graphite paste on FTO and on the [L –Fe(NO3 )] 2+ films for the measurement of switching behavior. The response ratio curve for the light-induced frequency-switching phenomena has been obtained. The frequency taped here is the oscillation frequency of the photo-generated electron and the hole in an exiton. Thus, the light-induced frequency-switching behavior and Schottky barrier diode characteristics of the material were established.